2010
DOI: 10.1007/s10439-010-9905-9
|View full text |Cite
|
Sign up to set email alerts
|

Towards Non-thrombogenic Performance of Blood Recirculating Devices

Abstract: Implantable blood recirculating devices have provided life saving solutions to patients with severe cardiovascular diseases. However, common problems of hemolysis and thromboembolism remain an impediment to these devices. In this article, we present a brief review of the work by several groups in the field that has led to the development of new methodologies that may facilitate achieving the daunting goal of optimizing the thrombogenic performance of blood recirculating devices. The aim is to describe work whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 91 publications
1
66
0
Order By: Relevance
“…An important phenomenon in these devices is that of flow separation, whereby coherent patterns of laminar flow become disrupted by blood flowing in a direction opposite to the main direction of flow, forming a low-velocity recirculation eddy. The resultant slowing and stagnation of the bloodstream can promote thrombus formation and development (24). The Palindrome catheter was found to have the largest regions of flow separation, with these regions most prominent around the distal tip and the side slots of the catheter.…”
Section: Discussionmentioning
confidence: 99%
“…An important phenomenon in these devices is that of flow separation, whereby coherent patterns of laminar flow become disrupted by blood flowing in a direction opposite to the main direction of flow, forming a low-velocity recirculation eddy. The resultant slowing and stagnation of the bloodstream can promote thrombus formation and development (24). The Palindrome catheter was found to have the largest regions of flow separation, with these regions most prominent around the distal tip and the side slots of the catheter.…”
Section: Discussionmentioning
confidence: 99%
“…is the vector with all unknown nodal vorticity values to be solved for our domain. To evaluate the integrals in Equations [8] and [9], we used a four-point quadrature scheme (42), and considered the the fact that v ðxÞ was optimally approximated by v FEM ij ðxÞ at the Gauss points. To reduce the computational effort to solve Equation [7] without compromising its accuracy, the matrix M was replaced by a diagonal lumped matrix M~, where…”
Section: Estimation Of the Vorticity Vector Fieldmentioning
confidence: 99%
“…A few studies of vorticity and helicity-related parameters have shown that these parameters have a direct relationship with geometric changes of the vessels and the reappearance of different diseases (7,8). Studies based on 3D cine PC-MRI performed on phantom data have revealed that vortex and helical flow can induce vessel wall injury and vascular remodeling (7,(9)(10)(11). Additionally, other studies have demonstrated that standard surgical procedures induce local and global hemodynamic changes of the treated section, altering the secondary flow patterns, which could lead to the reappearance of the pathology and the need for re-intervention (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…These devices are highly effective and applied frequently in patients with CVD. However, the host responses following deployment could induce complications like thrombosis and restenosis [1,2]. To minimize these responses, a protective surface coating is crucial for the safety as well as the lifetime of an implanted device.…”
Section: Introductionmentioning
confidence: 99%